Anatolian J Cardiol 2021
DOI: 10.5152/anatoljcardiol.2021.26020
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of atrial fibrillation and its effects on long-term follow-up outcomes in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction

Abstract: Objective: The incidence of atrial fibrillation (AF) in patients with ST segment elevation myocardial infarction (STEMI) varies between 7% and 21%, and most of these studies were in the thrombolytic era. However, the frequency of new-onset AF during the primary percutaneous coronary intervention (PCI) period is still unclear. We aimed to investigate the frequency of new-onset AF and its effects on long-term clinical events in patients undergoing primary PCI. Methods: A total of 1,603 patients who were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
7
1
2
Order By: Relevance
“…Arslan et al (9) reported that the there was no statistical significant difference between both groups regarding to Killip classification.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Arslan et al (9) reported that the there was no statistical significant difference between both groups regarding to Killip classification.…”
Section: Discussionmentioning
confidence: 92%
“…Also, Arslan et al (9) reported that the there was a high Statistical significant difference between both groups regarding CHA2DS2-VASc score (1.6±1 versus 2.7±2 ; P < 0.001). while Li et al (8) found that mean CHA2DS2-VASc scores significantly differed between the AF group and the non-AF group (4.09±1.38 and 3.27±1.51, respectively; P<.001).…”
Section: Discussionmentioning
confidence: 93%
“… 15 In previous studies, the prevalence of NOAF varied, with reports of 9.3% and 10.1% by Khalfallah and Elsheikh 13 and Aksoy et al, 7 respectively. Arsalan et al 16 reported a prevalence of 6.1%, and Selçuk et al 15 reported 8% among STEMI patients following primary PCI. However, Topaz et al 17 reported AF in 7.4% of cases, with only 2.8% representing NOAF.…”
Section: Discussionmentioning
confidence: 99%
“…На начало исследования между исследуемыми группами по сывороточной концентрации β-эндорфина статистически значимых различий не выявлено (p > 0,05). (3,6) 4,4 (3,5) MW-test p = 0,8847 p = 0,3517 p = 0,8794 p = 0,3234 Dunn's test, p 1-2 0,0107 0,0036 0,0303 0,0036 0,1777 0,0061 0,1457 0,9999 5-е сутки 849 (374, 224 5) 86 (48,5) 30 (20,35) 45, 3 (20,35-50) 15,3 (10,65-23,55) 4,4 (4,15-4,7) 4,5 (3,8) MW-test p = 0,0071 p = 0,0043 p = 0,0007 p = 0,9478 Dunn's test, p 2-3 0,0107 0,0036 0,0061 0,0036 0,0018 0,0027 0,9999 0,9999 10-е сутки 180 (113,9-242,2) 77 (59, 21,5 (12,45) 11,8 (6,(15)(16)(17)(18)(19)95) 6,1 (3,7-23, 0,0001 0,0001 0,0001 0,0001 0,0001 0,0001 0,3098 0,9999 В группе 2 на 5-е сутки на фоне применения ТЭС-терапии концентрация β-эндорфина была выше на 38,3%, чем в группе сравнения (p < 0,05). На 10-е сутки в основной группе сывороточная концентрация β-эндорфина была выше на 35,0%, чем в группе сравнения (p < 0,05).…”
Section: рисунок 1 характеристика межгрупповых различий в значении га...unclassified
“…Чрескожная траслюминальная коронарная ангиопластика (ЧТКА) со стентированием является одним из наиболее перспективных высокотехнологичных методов малоинвазивного хирургического лечения инфаркта миокарда (ИМ) [1]. Наряду с очевидной пользой ЧТКА при лечении ИМ, существуют также определенные риски, к их числу относят нарушения ритма сердца (НРС) [2,3]. Известно, что НРС развиваются в ≈5% случаев после проведения ЧТКА при лечении ИМ и оказывают негативное влияние на исход заболевания [1].…”
Section: Introductionunclassified